Nematode fauna of fish in Armenia - A. R. Hakobyan; V. V. Abrahamyan; O. V. Shcherbakov; A. S. Ghazaryan; V. V. Grigoryan; L. H. Grigoryan (Российский паразитологический журнал, 2024)
The purpose of the research is to study the species composition of nematodes dwelling in fish in natural reservoirs and on artificial pond fish farms in Armenia.Materials and methods. The studies were performed at the Research Center for Veterinary Medicine and Veterinary and Sanitary Expertise of the Armenian National Agrarian University and at the Laboratory of Molecular Parasitology of the Scientific Center of Zoology and Hydroecology from March 2020 to December 2022. Traditional ichthyo-parasitological methods were used to study 246 fish of 10 species from fish farms in the Ararat and Armavir Regions, from Lake Sevan and the Sevjur, Hrazdan, Marmarik, Akhuryan and Debed Rivers, as well as the Yerevan, Aparan and Akhuryan reservoirs. The study results were statistically processed (descriptive statistics) using the BioStat software.Results and discussion. The fish were found to have four types of nematodes: Contracaecum microcephalum Rudolphi, 1819, Philometroides sanguineus Rudolphi, 1819, Rhabdochona fortunatowi Dinnik, 1933 and Cystidicola farionis Fischer, 1798. Parasites were found in the body, on the serosa, in the air bladder walls, the intestinal lumen and the caudal fin thickness. The total nematode infection rate in fish was 9.76%. The nematode infection rate in fish was characterized by low values of prevalence and intensity other than the infection by the species Rh. fortunatowi (up to 24 specimens per fish). Among the found nematodes, the species C. microcephalum posed a potential threat to human health.